REPRESENTASI TOKOH PEREMPUAN DALAM FILM CINTA SUBUH KARYA ALI FARIGHI - Ma’arif, Moh. Syamsul; hikmah, miftahul (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to explain the depiction of women in the film 'Cinta Subuh' directed by Ali Farighi. There are many gender differences between men and women, including differences in status, roles, and responsibilities. This problem arises when women have limited opportunities compared to men who have extensive opportunities related to community programs and activities. This type of research is qualitative descriptive research. The data source is from the film